Предмет: Алгебра,
автор: Аноним
решите уравнение
(x-2)(x-3)=x(x+1)
(x+4)(x+6)-x^2=30
(x-5)(x+1)-x=x^2+5
(x-1)(x-3)=(x-2)(x-4)
Ответы
Автор ответа:
0
1. (x-2)(x-3)=x^2+x
X^2-5x+6-x^2-x=0
-6x=-6
X=1
2. (X+4)(x+6)-x^2-30=0
X^2+10x+24-x^2-30=0
10x=6
X=0,6
X^2-5x+6-x^2-x=0
-6x=-6
X=1
2. (X+4)(x+6)-x^2-30=0
X^2+10x+24-x^2-30=0
10x=6
X=0,6
Похожие вопросы
Предмет: Химия,
автор: rodionovy78
Предмет: Қазақ тiлi,
автор: anastasiya20041118
Предмет: Английский язык,
автор: gost228666
Предмет: Алгебра,
автор: ElenaL98
Предмет: Литература,
автор: sao1984